Hairy cell leukaemia and occupational exposure to benzene. - Clavel, J (1996)
OBJECTIVES: The role of occupational exposures in hairy cell leukaemia (HCL) was investigated through a multicentre, hospital based, case-control study. This paper analyses the role of exposure to benzene in HCL. METHODS: A population of 226 male cases of HCL and 425 matched controls were included in the study. Benzene exposure was evaluated by expert review of the detailed data on occupational exposures generated by case-control interviews. RESULTS: No association was found between HCL and employment in a job exposed to benzene (odds ratio (OR) 0.9 (95% confidence interval (95% CI) 0.6-1.3)). The sample included 125 subjects, 34 cases (15%), and 91 controls (21%) who had been exposed to benzene, as individually assessed by the experts, for at least one hour a month during one of their jobs. Benzene exposure was not associated with a risk of HCL (OR 0.8 (0.5-1.2)). No trend towards an increase in OR was detected for increasing exposures, the percentage of work time involving exposure to > 1 ppm, or the duration of exposure. No findings suggested a particular risk period, when the OR associated with the time since first or last exposure, or since the end of exposure, were examined. CONCLUSIONS: In conclusion, with the low exposures prevalent in the sample, the study did not show any association between benzene exposure and HCL.